The Biological and Cultural Grounds for Ethics: Hans Jonas and Francisco Ayala - Quesada-Rodríguez, Francisco (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
Regarding the epistemological borderlines between science and philosophy, this article approaches the human mind and ethics from biological and philosophical theories. For this purpose, the Darwinian theory of evolution by natural selection provides a scientific foundation to understand the human mind and ethics. However, not only Charles Darwin has studied mental faculties and ethics, this is also a topic researched by eminent contemporary paleontologists and biologists. Prior to modern biology, going back to Greek philosophy, philosophers have traditionally studied the human mind and ethics, separating human beings and the rest of nature ontologically. Following modern biology, the philosopher Hans Jonas has developed a philosophical biology from the perspective of hermeneutical phenomenology to understand life. With the help of his hermeneutical phenomenology, Jonas has presented an ontological theory of organism-metabolism to understand the phenomenon of life from simple living beings to the human mind in relation to nature, based on the body. Recently, the evolutionary biologist Francisco Ayala has proposed a coherent scientific and philosophical theory about biological and cultural roots for ethics, considering the evolution of human mental and intellectual capacities and the three conditions for ethical behavior as a part of human intellectual capacity, which scientifically complements and informs Hans Jonas’s philosophical biology and ethics of responsibility.
Keywords: Darwin; Ayala; Jonas; The Phenomenon of Life; Hermeneutical Phenomenology; Ontology; Bioethics; Natural Sciences